The Impact of Direct Cash Assistance (BLT) on Community Welfare - Asdar, Asdar; Jam'an, Andi; Ms, Basuki Rahmat; Naidah, Naidah; Tahir, Nur Alfilahi (Jurnal Ekonomi Balance, 2024)
The aim of this research is to determine the impact of Direct Cash Assistance (BLT) on the welfare of the community in Pa'rappunganta Village, North Polongbangkeng District, Takalar Regency. This research is qualitative in nature with data obtained from informants through observation and interview methods. The data used includes primary data originating directly from the community and secondary data obtained from official documents at the research location. Direct Cash Assistance (BLT) is a form of government social intervention that aims to help poor people, especially in meeting their basic needs. Based on research results, BLT has a significant role in alleviating the economic burden on poor communities in the short term. However, the impact of BLT is not strong enough to improve the quality of life of the poor as a whole, let alone reduce the poverty rate in the region. This is due to the temporary and unsustainable nature of the BLT program. This program only provides a temporary solution without providing opportunities for people to get out of poverty systematically. Apart from that, there are obstacles in implementing the program, such as unequal distribution and lack of supervision, which causes the effectiveness of this program to be limited. This research concludes that although BLT helps reduce temporary economic pressure, more integrated and sustainable policies are needed to achieve long-term goals of increasing welfare and alleviating poverty in Pa'rappunganta Village. Community empowerment programs such as skills training and increasing access to employment opportunities can be a more effective alternative solution.